ENHANCING CRITICAL THINKING SKILLS AT THE LESSONS OF FOREIGN LANGUAGE (Konferensiyalar | Conferences, 2024)
Critical thinking denotes individuals' capacity to autonomously think and make accurate decisions. Presently, fostering critical thinking among learners is regarded as a crucial responsibility of foreign language instructors, given its significant role in language classrooms. Numerous factors influence the critical thinking skills of language learners, with assessment methods being one of them. Thus, by effectively managing how language learners' abilities are assessed, instructors can facilitate the development of their critical thinking skills. This presentation will offer suggestions for language teachers to select appropriate assessment methods and activities.